2010
DOI: 10.1002/jso.21645
|View full text |Cite
|
Sign up to set email alerts
|

Clinically significant thromboembolic disease in orthopedic oncology: An analysis of 986 patients treated with low‐molecular‐weight heparin

Abstract: Despite general oncologic and orthopedic factors favoring VTE, the clinical occurrence of this event was extremely low in this series, probably due to a consistent and careful prophylaxis, prolonged until the time of complete weight-bearing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…In this study, the incidence of DVT was comparable to Kim et al, Mitchell et al, Patel et al, and Benevenia et al, even though our patients were asymptomatic. There are few retrospective studies reporting a lower incidence of DVT in patients who underwent oncology lower limb surgery (Heit et al 2000 ; Mitchell et al 2007 ; Ramo et al 2011 ; Ruggieri et al 2010 ). The incidence ranged from 1.1 to 2.4 % for DVT and 0.1 to 2.3 % for PE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the incidence of DVT was comparable to Kim et al, Mitchell et al, Patel et al, and Benevenia et al, even though our patients were asymptomatic. There are few retrospective studies reporting a lower incidence of DVT in patients who underwent oncology lower limb surgery (Heit et al 2000 ; Mitchell et al 2007 ; Ramo et al 2011 ; Ruggieri et al 2010 ). The incidence ranged from 1.1 to 2.4 % for DVT and 0.1 to 2.3 % for PE.…”
Section: Discussionmentioning
confidence: 99%
“…Ramo et al ( 2011 ) studied the incidence of DVT in 423 patients who underwent endoprosthesis replacement and he concluded that the incidence of symptomatic venous thromboembolism in their group of cancer patients who underwent lower-extremity endoprosthetic arthroplasty was lower than anticipated. Ruggieri et al ( 2010 ) looked at his population of 986 patients with uncemented endoprosthesis. He concluded that the clinical occurrence of this DVT was extremely low probably due to a consistent and careful prophylaxis, prolonged until the time of complete weight-bearing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9] It is, however, extremely difficult to compare the incidence of VTE from the literature, because the characteristics of the patients, the type of VTE prophylaxis and the method of DVT detection differ between reports.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] However, a small number of studies have shown that there is a risk of significant venous thromboembolism (VTE). [4][5][6][7][8][9] VTE, which includes deep-vein thrombosis (DVT) and pulmonary thromboembolism (PTE), is recognised as a serious complication of major surgery. Patients undergoing operations for cancer and orthopaedic surgery on the lower limbs are at particular risk.…”
Section: Cite This Article: Bone Joint J 2013;95-b:1280-4mentioning
confidence: 99%